The Effects Of Lubrication On The Rolling Contact Surface Deformation - Foo, Chun Yit (Universiti Sains Malaysia, 2019)
Lubrication plays an important role to prevent or reduce friction between two surfaces. In rolling contact, the lubricant forms a layer of film to separate the rolling surfaces and to sustain the applied load. Insufficient lubrication normally results in severe surface deformation and wear promoting short operation life. In this work, the effects of lubrication on the rolling surface contact deformation were studied using cylindrical roller bearing. Two sets of experiments were carried out to compare the surface deformation of a dry roller bearing and a lubricated roller bearing. The dry bearing was run by an AC motor with 1500 rpm, the surface roughness of inner race was measured every 30 minutes until it failed. Whereas for lubricated bearing, the surface roughness of inner race was measured by every 10 hours until 100th hour was reached. Vibration level was measured at the beginning and at the end of experiments. The surface topography and surface asperities profile analysis results show that the surface deformation is severe for un-lubricated dry bearing where small micro pitting groove was formed and there is an accumulation of removed material particles on the surface. For the lubricated bearing, surface deformation is very low and it is expected that the grease has a capability to remove the particles and avoided them from accumulating on the surface. Besides, the dry bearing was damaged and sparks occurred at 105th minutes while lubricated bearing was still operating smoothly after rotating for 100 hours. This showed that lubricant prolonged the life span of the bearing efficiently. The lubrication film thickness over root mean square roughness parameter (λ) is determined by the Hamrock-Dowson equation which showed that the grease lubricated bearing operated at λ = 0.3 which is under boundary lubrication. For surface roughness analysis, it is observed that the RMS surface roughness and kurtosis of the lubricated inner race were lower as compared to the surface of dry inner race. The surface of lubricated inner race had low negative skewness value while surface of the dry inner race has high positive skewness value. From RMS vibration acceleration level analysis, it is observed that the lubricant managed to reduce the vibration of the bearing. Without lubrication, the vibration level is very high during bearing failure which is at 1.71 while only 0.32 m/s2 of vibration level was obtained after 100 hours of operation in lubricated condition.